Conflicts of sports science with the practice of Physical Culture and Sports - N. V. Filonenko (Путеводитель предпринимателя, 2020)
The article describes the socio-economic and legal aspects of the development budget sports complex of marketing means of paid services, analyzes the problem of the relationship of sports science to physical education and sport management practices, outlines possible solutions to problems.